UPAYA MENINGKATKAN PENYESUAIAN DIRI SISWA PADA PROSES PEMBELAJARAN OLEH GURU SOSIOLOGI DIKELAS X MAN FILIAL - Huda, Nurul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstrackThe title of this research is Efforts to Improve Student Adjustment In Learning Process By Sociology Teacher In Class X IIS MAN 2 Filial Pontianak. The sub-problems in this research are how the sociology teacher seeks to improve students' self-adjustment in the form of creating a fun learning atmosphere for students in the learning process in class X IIS MAN 2 Filial Pontianak? And How is the sociology teacher trying to improve students 'self adjustment using learning method that encourages students' learning spirit in learning process in class X IIS MAN 2 Filial Pontianak ?. The purpose of this study is to describe Efforts to Improve Student Adjustment In Learning Process By Sociology Teacher In Class X IIS MAN 2 Filial Pontianak. This research uses qualitative approach by using descriptive method. Data collecting technique through observation, interview and documentation study. The data collection tool used is an observation guide and an interview guide. The results showed that: there are various forms of efforts by teachers to improve students' self-adjustment in the form of creating a fun learning that is: 1. inserting lucuan-lucuan when delivering the material, 2. appreciating the opinions and answers of learners, 3. not showing anger And always smiling at the time of teaching, 4. giving understanding and confidence to the students so as not afraid to answer, 5. giving awards in the form of praise and appreciation niai. The method used is the lecture method, and the method of frequently asked questions, which is often used is a question and answer method that encourages the spirit of learning learners.Â Keywords: Student Adjustment, Learning Process, Sociology Teacher